PENERAPAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA PERANCANGAN SISTEM INFORMASI PENJUALAN ALAT KESEHATAN PADA CV. ELANG MEDIKA BATURAJA - Faulina, Sri Tita; Wisnumurti, Wisnumurti; Lestari, Novi (JIK : Jurnal Informatika dan Komputer, 2023)
Information System is a system that is needed as a tool, in data processing with speed, accuracy, and efficiency. Medical Device Sales Information System at CV. Elang Medika Baturaja Using Embarcadero XE2, is a CV that does not use a computer in data processing. This research was conducted by visiting CV. Elang Medika Baturaja, using data collection methods such as interviews, observations, references, and book and journal sources. In making this Medical Device Sales Information System, this system was built using the Rapid Application Development (RAD) method which can help work on making medical device sales information systems faster and of course have quality in meeting user needs both in terms of time, cost and also effort The result of this research is a medical device sales information system at CV. Eagle Medika is designed to be able to help CV. Elang Medika in processing data and facilitating transaction and data search, as well as producing fast and accurate reports.